2022
DOI: 10.1109/trpms.2021.3060191
|View full text |Cite
|
Sign up to set email alerts
|

Fast Monte Carlo-Based Inverse Planning for Prostate Brachytherapy by Using Deep Learning

Abstract: Inverse planning is an essential tool for optimizing the delivered radiation dose on low-dose-rate (LDR) prostate brachytherapy. Clinical inverse planning systems use the TG-43 dose computation formalism in order to perform a fast optimization. However, this method is an approximation that often leads to a dose overestimation, resulting on sub-optimal plans. Alternatively, Monte Carlo simulation (MCS) can be used to obtain an accurate dose distribution, but considerably increasing the estimation time. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The similar initialization settings with the number of needles were also applied in inverse treatment planning of low-dose-rate prostate brachytherapy. 10 In other planning methods, 21,33 the number of seeds was calculated using empirical formulas, while the number of needles was optimized as a parameter. Although the DVH metrics of the dose distribution demonstrate the advantage of knowledge-based initialization, in the future, we plan to investigate the impact of reducing the number of needles on the quality of the generated plans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The similar initialization settings with the number of needles were also applied in inverse treatment planning of low-dose-rate prostate brachytherapy. 10 In other planning methods, 21,33 the number of seeds was calculated using empirical formulas, while the number of needles was optimized as a parameter. Although the DVH metrics of the dose distribution demonstrate the advantage of knowledge-based initialization, in the future, we plan to investigate the impact of reducing the number of needles on the quality of the generated plans.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, no TPS has been specifically developed for LDR brachytherapy of liver malignancies, and hence, we can only compare the execution time of our TPS to those utilized in other clinical applications. Villa et al 21 reported an execution time of approximately 1 min for their prostate brachytherapy plan generation, excluding GTV and OAR contouring. Guthier et al 10 reported an execution time of approximately 35 s for their inverse treatment planning, which also does not include GTV and OAR contouring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual design of plan is often necessary, and the quality of the plan depends heavily on the clinician's experience. Efforts have been made to develop automatic SIBT planning methods to improve planning efficiency and quality consistency 14–17 . However, current methods are primarily designed for seed position optimization within possible parallel needle paths determined by co‐planar templates 17 and are not suitable for H&N SIBT due to complex anatomy and ample path blockages by bones, vessels, and other OARs.…”
Section: Introductionmentioning
confidence: 99%
“…As the most accurate dose calculation method, Monte Carlo simulation (MCS) has been widely applied in the plan dose evaluation for brachytherapy. However, its high computation complexity hinders the usage in routine clinical planning 15,22 . To facilitate accurate dose evaluation during plan optimization, several endeavors have been made to develop fast analytical dose computation methods by modifying the TG‐43 formula to account for heterogeneous tissue 23–27 .…”
Section: Introductionmentioning
confidence: 99%